Building collagen IV smart scaffolds on the outside of cells - Brown, Kyle L. (Protein Sci, 2017)
Collagen IV scaffolds assemble through an intricate pathway that begins intracellularly and is completed extracellularly. Multiple intracellular enzymes act in concert to assemble collagen IV protomers, the building blocks of collagen IV scaffolds. After being secreted from cells, protomers are activated to initiate oligomerization, forming insoluble networks that are structurally reinforced with covalent crosslinks. Within these networks, embedded binding sites along the length of the protomer lead to the “decoration” of collagen IV triple helix with numerous functional molecules. We refer to these networks as “smart” scaffolds, which as a component of the basement membrane enable the development and function of multicellular tissues in all animal phyla. In this review, we present key molecular mechanisms that drive the assembly of collagen IV smart scaffolds.